1960
DOI: 10.1017/s0007485300055152
|View full text |Cite
|
Sign up to set email alerts
|

Trapping as a means of studying the game tsetse, Glossina pallidipes Aust.

Abstract: In an area of sleeping sickness due to Trypanosoma rhodesiense in Uganda, Morris's ‘ animal ’ traps were used to study the activity and the relations with habitat and hosts of the vector, Glossina pallidipes Aust., a tsetse difficult to sample by conventional fly-round methods.This type of trap was found to give samples both numerically greater and more truly representative of the tsetse population present than did either fly-boys or Chorley's bicycle screen.Black traps showed an over-all superiority to brown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Curson (1924) found two activity peaks. Morris (1960) reported a midday peak, while Smith & Rennison (1961), Pilson & Leggate (1962), Harley (1965) and Jaenson (1978) reported major activity in the late afternoon. Morris (1960) reported a midday peak, while Smith & Rennison (1961), Pilson & Leggate (1962), Harley (1965) and Jaenson (1978) reported major activity in the late afternoon.…”
mentioning
confidence: 99%
“…Curson (1924) found two activity peaks. Morris (1960) reported a midday peak, while Smith & Rennison (1961), Pilson & Leggate (1962), Harley (1965) and Jaenson (1978) reported major activity in the late afternoon. Morris (1960) reported a midday peak, while Smith & Rennison (1961), Pilson & Leggate (1962), Harley (1965) and Jaenson (1978) reported major activity in the late afternoon.…”
mentioning
confidence: 99%
“…Since a natural tsetse population contains about 20% males and 80% females (Morris, 1960;Glasgow & Duffy, 1961), a suitable sampling technique is one that catches males and females in the proportion of 1:4. In this respect the Langridge-trap method is better for sampling G. pallidipes than is the fly-round which catches more males than females.…”
Section: Discussionmentioning
confidence: 99%
“…A particular host species, with high population density, in a tsetse habitat may cause more flies to feed on it. BARRAS (1960BARRAS ( , 1970, MORRIS (1960), HARLEY (1963), SMITH and RENNISON (1961) and SAUNDERS (1964) showed that tsetse are attracted to dark colours, while FULLER and MOSSOP (1929) noted the attractiveness of shaded cavities which are mistaken for the belly of an animal. WEITZ (1963), on examination by immunological methods of 22,640 blood-meal squashes from 15 Glossina species in East Africa, concluded that each species has its characteristic behaviour not dependent on availability of the different hosts and further suggested that feeding habits are genetically determined.…”
Section: Host Selection and Feeding Patternmentioning
confidence: 99%
“…Although impala, wildebeest, waterbuck, and particularly zebra occurred in large numbers in collection areas, they were ignored. Darker colours are not necessarily the most attractive (MORRIS, 1960;SAUNDERS, 1964). Adaptation to new hosts is therefore possible.…”
Section: Host Selection and Feeding Patternmentioning
confidence: 99%